2009
DOI: 10.3390/su1030556
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Attitudes and Behaviour to Household Waste Management in Cameroon to Drive Strategy Development: A Q Methodological Approach

Abstract: Household waste is an environmental and public health problem, especially for the large cities in Sub-Saharan African countries. While the improper management of household waste in Cameroon is linked to the systematic failure of policy makers and municipal authorities to identify the most sustainable ways of dealing with it in such a manner that is in line is with their socio-economic aspirations, the impact of public attitudes and behaviour has been neglected. It is in this context that this paper uses Q-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Attitude is difficult to define, and even within the expert psychological realm, there is little agreement as to what is understood by it (Mbeng et al, 2009). With that statement, the context of attitude in this study was focused on determining beliefs, behaviours, and attitudinal factors of household chemical poisonings.…”
Section: Attitudementioning
confidence: 99%
“…Attitude is difficult to define, and even within the expert psychological realm, there is little agreement as to what is understood by it (Mbeng et al, 2009). With that statement, the context of attitude in this study was focused on determining beliefs, behaviours, and attitudinal factors of household chemical poisonings.…”
Section: Attitudementioning
confidence: 99%
“…Mckay et al (2015) identified inadequate organizational structure; poor logistical support; lack of capital and technical expertise; inhibiting government policy and regulations; as well as low levels of awareness and education at the household level as the main inhibitors of growth in this sector. Mbeng et al (2009) in their study reported that although information and awareness campaign are important drivers to behavior change in waste management, these do not necessarily translate into an increased participation in recycling or reuse initiatives because other factors such as economic incentives can hamper participation rate. These studies have so far, explored issues related to the participation of the private sector and public attitudes and awareness in the solid waste sector; they do not however address residents" willingness to pay (WTP) for solid waste management.…”
Section: Introductionmentioning
confidence: 96%
“…Studies have shown a strong concern among people for a clean environment and the belief that learning, information and awareness campaigns are important drivers to behaviour change (Mbeng et al, 2009). However, this does not necessarily translate into an increased participation in recycling or reuse initiatives.…”
Section: Lack Of Environmental Awareness In Societymentioning
confidence: 99%